Toll-like Receptor (TLR) dan Imunitas Natura - Suprapto Ma’at (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
In all living species, the first line of defence against microbial aggressions is constituted by innate immunity. Toll-like receptors(TLRs) are a family of pattern recognition receptors that are activated by specific components of microbes and certain host molecules.They constitute the first line of defense against many pathogens and play a crucial role in the function of the innate immune system.Recognition of pathogen-associated molecular pattern (PAMP) by TLR, alone or heterodimerization with other TLR or non-TLR receptors,induces signals responsible for the activation of genes important for an effective host defense, especially proinflammatory cytokines, orinitiates signal transduction pathways, which trigger expression of genes. These gene products control innate immune responses andfurther instruct development of antigen-specific acquired immunity.